Prediction Cell Parameter of A2MX6 Cubic Perovskites - Hadda Krarcha; Abdelhak Ferroudj (Revue des Énergies Renouvelables)
A2MX6 perovskites materials have shown impressive advances in the last 50 years due on their photovoltaic application, made them one of the most-promising technologies for next-generation solar cells. We present in this work a semi empirical model for prediction of cell parameter of cubic A2MX6 perovskites. It is useful for providing the predicted structural information for estimating the physical properties of materials for which accurate structural data are not available. We propose a linear formula  according to the factors:  Interatomic distance RA + RX and RM + RX and electronegativity difference .  The interatomic distances dX-X and  dM-Xd can be estimated from the crystalline structure of the compounds studied.    A new prediction of cell parameter is estimated for 90 perovskites and the results are compared with the experimental one whose error is of the order of 1.13%.